The deficiency of tumor suppressor prep1 accelerates the onset of meis1- hoxa9 leukemogenesis. - Leila Dardaei; Livia Modica; Giorgio Iotti; Francesco Blasi (PLoS ONE, 2014)
Prep1 and Meis1 ortholog TALE transcription factors have opposing roles in tumorigenesis: Meis1 serves as an oncogene, Prep1 as a tumor suppressor. We now report that, Meis1 overexpression in primary Prep1-deficient (Prep1i/i) embryonic hematopoietic cells increases self-renewal potential of cells in vitro but not in vivo, whereas leukemia is instead obtained when Meis1 is combined with another oncogene, HoxA9. Prep1i/i Meis1-HoxA9-generated leukemic cells are less differentiated and grow more aggressively after the second passage in the mouse. These data indicate that Prep1 represents a barrier to the transforming activity of Meis1 in vitro, but its absence is not sufficient to induce early leukemogenesis. On the other hand, the Prep1i/i background appears to favor the insurgence of mutations that cause a more aggressive Meis1-HoxA9-generated leukemia. Indeed, the Prep1i/i leukemic cells upregulate the Polycomb protein Bmi-1 and expectedly down-regulate the Ink4a/Arf locus products. Finally, an important feature contributed by the Prep1i/i background is the post-transcriptional increase in Meis1 protein level.